Literature Review: Psychological Impact on Early Age Marriage - Pranandia, Salsabila Lintang; Aisyaroh, Noveri; Adyani, Kartika (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2024)
Background: Cases of early marriage continue to increase throughout the world, around 650 million women get married before they are 18 years old. Early marriage triggers poor mental health related to the economy, caring for children and family traditions. Objective: To discuss the psychological impact of early marriage. Method: Using the Literature Review method, search for articles using Google Scholar and Pubmed in the last 5 years. Results: From 7 international and national articles, it was found that the psychological impacts that occur in young women marrying early are stress, anxiety and depression, depression and trauma. Conclusion: The psychological impact of early marriage is stress, anxiety and depression, depression and trauma